Pendampingan Siswa SMK Kristen Surakarta dalam Penyajian Hasil Produk Pastry - Truli Nugroho; Suryo Adinugroho; Yusak Prakoso; Alexander Mario Retto Djong; Kristian Faskahariyanto (Pusat Riset dan Inovasi Nasional, 2025)
This community service activity aims to enhance the pastry presentation skills of students at SMK Kristen Surakarta, focusing on professional and aesthetic standards. Presentation is the final stage in food production and influences consumer perceptions. The mentoring process included technical guidance, demonstrations, and hands-on practice aligned with industry standards. Through this program, students gained both theoretical understanding and practical competency in presenting pastry products. Evaluation results show notable improvements in students’ ability to apply principles of aesthetics, hygiene, and presentation structure. The program also fostered students' confidence and job-readiness for future careers in the hospitality and food industries.